2011
DOI: 10.1128/jcm.01392-10
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Real-Time PCR Assay for Detection and Quantification of Blastocystis Parasites in Human Stool Samples: Prospective Study of Patients with Hematological Malignancies

Abstract: Blastocystis anaerobic parasites are widespread worldwide in the digestive tract of many animal species, including humans. Epidemiological Blastocystis studies are often limited by the poor sensitivity of standard parasitological assays for its detection. This report presents a highly sensitive real-time quantitative PCR (qPCR) assay developed to detect Blastocystis parasites in stool samples. The assay targets a partial sequence of the Blastocystis small ribosomal subunit (SSU) rRNA gene, allowing subtyping (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
168
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 38 publications
15
168
1
4
Order By: Relevance
“…However, the real prevalence of the parasite in this geographic area could greatly be underestimated because nonmolecular methods have a low diagnostic sensitivity compared with qPCR. 5 The present study confirms this observation, since 17 of 100 DLMnegative samples were subsequently shown to be positive for Blastocystis sp. by qPCR.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…However, the real prevalence of the parasite in this geographic area could greatly be underestimated because nonmolecular methods have a low diagnostic sensitivity compared with qPCR. 5 The present study confirms this observation, since 17 of 100 DLMnegative samples were subsequently shown to be positive for Blastocystis sp. by qPCR.…”
supporting
confidence: 78%
“…1 It has also been shown that prevalence data may depend on detection methods, especially direct-light microscopy (DLM) of fecal smears versus polymerase chain reaction (PCR) assays. 5 For many years, Blastocystis sp. was considered with no clinical relevance mainly because asymptomatic colonization is very common.…”
mentioning
confidence: 99%
“…However, prevalence data are largely dependent on the methods used for detection, quantitative PCR being the most sensitive method, meaning that infections by Blastocystis sp. are likely underestimated [7,15].…”
Section: Discussionmentioning
confidence: 99%
“…The first study [21] was able to detect ST1, ST3 and ST4 but it is unknown whether other subtypes are able to be detected using this assay and therefore the specificity and sensitivity is unknown. The second study designed a genus-specific PCR which was able to detect all known subtypes so far identified in humans [22]. This test only had 95% specificity though, and the amplicon size of 339 bp is much longer than usually desired for RT-PCR sensitivity.…”
Section: Typing Methodsmentioning
confidence: 99%
“…There have been two studies where ST1 was the predominant subtype with 51.4% of positive from this group belonging to this group in China, 41% in Brazil [17,33,34] and three others where ST4 was the predominant subtype with 63% in France, 84% in Nepal and 94.1% in Spain, with no ST3 identified in the Spain population [22,35,36]. From South American countries it is seen that there is a predominance of ST1, ST2 and ST3 with no other STs being isolated.…”
Section: Epidemiologymentioning
confidence: 99%